Initial Efficacy of a Cardiac Rehabilitation Transition Program: Cardiac TRUST - Dolansky, Mary A. (2011)
Patients recovering from cardiac events are increasingly using postacute care, such as home health care and skilled nursing facility services. The purpose of this pilot study was to test the initial efficacy, feasibility, and safety of a specially designed postacute care transitional rehabilitation intervention for cardiac patients. Cardiac Transitional Rehabilitation Using Self- Management Techniques (Cardiac TRUST) is a family-focused intervention that includes progressive low-intensity walking and education in self-management skills to facilitate recovery following a cardiac event. Using a randomized two-group design, exercise self-efficacy, steps walked, and participation in an outpatient cardiac rehabilitation program were compared in a sample of 38 older adults; 17 who received the Cardiac TRUST program and 21 who received usual care only. At discharge from postacute care, the intervention group had a trend for higher levels of self-efficacy for exercise outcomes (X=39.1, SD=7.4) than the usual care group (X=34.5; SD=7.0) (t-test 1.9, p=.06). During the 6 weeks following discharge, compared with the usual care group, the intervention group had more attendance in out-patient cardiac rehabilitation (33% compared to 11.8%, F=7.1, p=.03) and a trend toward more steps walked during the first week (X=1,307, SD=652 compared to X=782, SD=544, t-test 1.8, p=.07). The feasibility of the intervention was better for the home health participants than for those in the skilled nursing facility and there were no safety concerns. The provision of cardiac-focused rehabilitation during postacute care has the potential to bridge the gap in transitional services from hospitalization to outpatient cardiac rehabilitation for these patients at high risk for future cardiac events. Further evidence of the efficacy of Cardiac TRUST is warranted.